Chinese Expert Consensus on ovarian function and fertility preservation of cervical cancer in pregnancy (2023) - Ruan, Xiangyan (Frontiers in Endocrinology, 2023)
Cervical cancer in pregnancy (CCIP) refers to cervical cancer diagnosed during pregnancy, the most common gynecological malignant tumor. Because of the special physiological changes of CCIP, although preserving ovarian function and fertility is very important, the methods are very limited. There is no guideline or consensus on the preservation methods of ovarian function and fertility in this special period. Therefore, the Committee of Fertility Protection and Preservation of China Association for the Promotion of Health Science and Technology, combined with the Chinese Society of Gynecological Endocrinology affiliated to the International Society of Gynecological Endocrinology, Society Endocrinology Branch of Beijing Institute of Obstetrics & Gynecology, combined with Society on Fertility Preservation affiliated to Chinese Preventive Medicine Association, organized relevant experts from different disciplines to formulate this consensus, in order to guide ovarian function and fertility preservation of CCIP patients.